PELAKSANAAN PERJANJIAN KREDIT UNTUK MENCEGAH ADANYA KREDIT BERMASALAH DI BANK SINARMAS CABANG SINGARAJA - Anis Wijayanti (Universitas Pendidikan Ganesha, 2013)
ABSTRACTThis study aimed to determine: (1) The loan agreement with Bank Branch Sinarmas Singaraja Bali, (2) Being non-performing loans faced by the Bank Sinarmas, (3) Efforts - Efforts were made to resolve the legal issues in the Bank Sinarmas credit. This study used descriptive qualitative research approach. The technique of determining the subject of research using purposive sampling and snow ball the subject of this study is Chairman Sinarmas Bank Branch Singaraja, Employees of the credit from Bank Branch Sinarmas Singaraja, Debtor, Notary Public Employees Singaraja court. Data collection techniques used in this study: (1) observation, (2) interviews, (3) the recording of documents, (4) Method of literature. Tekniuk descriptive analysis with qualitative data analysis. These results indicate that (1) prior to the loan agreement executed, then the bank has provided a blank credit agreement are enforceable prior to credit given to each applicant, and if the debtor and the bank agreed with blank credit application is considered worthy to be given to the debtor the bank will provide Letters of Credit Confirmation that contains a large number or credit approval, loan repayment period, the amount of costs such as interest and other fees necessary, withdrawal of credit terms, manner and form of lines of credit and credit guarantees worth, (2) Being non-performing loans has ever faced by the Bank Sinarmas Branch Singaraja is substandard loans and non-performing loans (3) Prior to take legal action in the resolution of credit issues early - first Bank Sinarmas rescue efforts by providing a grace period and mengurangu lending rates. While the Court Alternative Dispute Resolution Singaraja give melelui negotiation, mediation and then arbitration.Keywords: Credit Agreement, Credit Problems.